Analisis Fenomena Day of the Week Effect: Pengujian Monday Effect, Week-Four Effect and Rogalski Effect (Studi Empiris pada Perusahaan LQ 45 di BEI) - Shinta Heru Satoto (Universitas Kristen Maranatha, 2011)
The purpose of this study were to provide an empirical evidence of the day of the week phenomenon in Indonesian Capital Market. This research used 39 sample firms that list on LQ 45 Indonesian Capital Market on January 1, 2009 until December 31, 2010. The results indicate that Monday returns are positive and significant on average, and significantly different from returns of the rest of the week. Thus, no evidence was uncovered to support Monday effect and week four effect in Indonesian capital market. Furthermore, the empirical result found that there was Rogalski effect in Indonesia capital market. It could be because the effect of financial report periods which force all firms to announce the report before the end of the financial report periods. This study indicating that stock market returns are consistent with the weak form of market efficiency.Keywords: day of the week effect, Monday effect, week-four effect, Rogalski effect